2015
DOI: 10.1007/978-3-662-48054-0_21
|View full text |Cite
|
Sign up to set email alerts
|

Network Creation Games: Think Global – Act Local

Abstract: We investigate a non-cooperative game-theoretic model for the formation of communication networks by selfish agents. Each agent aims for a central position at minimum cost for creating edges. In particular, the general model (Fabrikant et al., PODC'03) became popular for studying the structure of the Internet or social networks. Despite its significance, locality in this game was first studied only recently (Bilò et al., SPAA'14), where a worst case locality model was presented, which came with a high efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Concerning local coalitions, a notion of equilibrium close in spirit to our LSE has been studied in the context of network design games in [19]. Moreover, locality aspects have been also considered when restricting the strategy space in single-player deviations (see for example [4,10]).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning local coalitions, a notion of equilibrium close in spirit to our LSE has been studied in the context of network design games in [19]. Moreover, locality aspects have been also considered when restricting the strategy space in single-player deviations (see for example [4,10]).…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, a constant PoA was proven by Chauhan et al [15] for a version with non-uniform edge prices. In contrast, non-constant lower bounds on the PoA have been proven for local versions of the network creation game by Bilò et al [10,12] and Cord-Landwehr & Lenzner [18].…”
Section: Related Workmentioning
confidence: 99%
“…It was shown that the PoA may deteriorate heavily if agents only know their local neighborhood or only a shortest path tree of the network [8,9]. In contrast, a global view with a restriction to only local edge-purchases yields only a moderate increase of the PoA [11].…”
Section: Related Workmentioning
confidence: 99%